Teaching English: An afresh sophisticated technique to cultivate digital native learners’ vocabulary by utilizing seesaw media as digital literacy - Ikrar Genidal Riadil (Universitas Islam Malang, 2020)
In the modern and digital era, digital native’s learners are conceived into an era of digital networking. It keeps everything connected to technology. Digital natives with digital technical expertise and abilities which can theoretically be utilized for improved learners’ interaction in the classroom. The government has began to vigorously increase the literacy culture in schools by doing reading literacy. Teachers will be willing to provide an precedent by developing a community of literacy at school. Increased classroom reading atmosphere also improves vocabulary for learners studying English. The Seesaw Media implementation may also help learners to insert allusions to enhance scientific knowledge as a regulatory framework for learning. The aim of this research was to discern the use of Seesaw as the media of literacy to cultivate learners’ vocabulary. This research pursued to answer two research questions; (1) does Seesaw Media helps learners to improve their reading ability? And (2) what are the impacts of Seesaw Media application on the learners on developing vocabulary? The methods used by the researcher were; firstly, the researcher distributed the questionnaire with the English learner's. Secondly, the researcher assessed the feedback from the respondents. Thirdly, the researcher sought the response to the learners on the effect of reading ability by using Seesaw. This research has used descriptive qualitative to conduct the research study. This result of the research has shown the Seesaw Media helped learners to improve their reading ability.